Digital Marketing Communication Strategy to Increase Brand Awareness of Products at Mulyosari Group - Rizky, Zulfikar Khusnul Ghina; Majid, Nurkholish (Jurnal Multidisiplin Madani, 2023)
In the development of the business world, it is very important to be able to implement effective communication strategies, especially in the digital world era where product marketing is now all online. Because now consumers really see a product from its brand, in this case, brand awareness becomes important so that a business can compete in the market. To be able to increase brand awareness of a product, an effective communication strategy is needed so that it can be well received by consumers who will buy the product. The purpose to be achieved in this study is to be able to find out how to introduce or increase brand awareness to customers by using effective communication strategies in order to increase sales in the online market or marketplace. This research uses a descriptive qualitative method by conducting interview techniques with sources as well as field observations and documentation which will later be described in detail as the results of this research